BREAST FEEDING PRIORITIES: THE EXAMPLE OF ACTIVITY OF MATERNITY AND CHILDHOOD PROTECTION SERVICES IN BURYAT REPUBLIC - I.Yu. Tarmaeva ("Paediatrician" Publishers LLC, 2008)
The priority of breast feeding was observed taking into account a demographic setting in our country at present. The role of maternity and childhood protection services in Buryat republic in popularization of breast feeding was shown. The need of further introduction of new organizational technologies in improvement of health state of newborns was noted. Key words: breast feeding, maternity and childhood protection services, organizational technologies.